ROLE OF INTRAVENOUS HUMAN ALBUMIN IN MANAGEMENT OF NEONATAL HYPERBILIRUBINEMIA - Alrabaty, Abbas Abdulqadir; Ismael, Awat Shokri (Journal of Sulaimani Medical College, 2013)
Background Bilirubin is a known toxin to the newborn nervous system. Hyperbilirubinemia is treated by phototherapy and exchange blood transfusion; the intravenous infusion of human albumin can reduce the post-exchange serum bilirubin level and shorten duration of phototherpy and hence admission to hospital. Objectives To determine the role of intravenous administration of human albumin prior to exchange transfusion in term neonates with neonatal hyperbilirubinemia for reduction of serum bilirubin. Patients and Methods In this Study, fifty out-born term neonates with gestational age of >37 weeks and birth weight of >2500 grams, but otherwise healthy with high serum bilirubin required blood exchange immediately or after intensive phototherapy failure; were admitted to the neonatal unit of Raparin Pediatric Teaching Hospital in Erbil. The intervention group (n=25) received intravenous human albumin 20% (1 g/kg) one hour before exchange while the control group (n=25) underwent a blood exchange without intravenous human albumin. Results The mean total serum bilirubin (TSB) level in the albumin treated group was significantly lower than that in the control group at 6, 12 and 24 hours post-exchange (P<0.001). Mean duration of phototherapy was significantly reduced in the albumin treated group, compared to that in the control group (22.7±2.4 vs. 36±8.2 hours) respectively, (P<0.001). None of the neonates in the albumin treated group needed second exchange transfusion and no complications were observed. Conclusion Infusion of 20% albumin (1 g/kg) one hour prior to blood exchange transfusion can significantly reduce the post-exchange TSB, duration of phototherapy and the total duration of hospital admission.
Keywords: Intravenous Albumin; Neonatal Hyperbilirubinemia